Arbuscular mycorrhiza enhances nutrient accumulation in wheat exposed to elevated CO2 and soil salinity. Issue 6 (13th September 2018) - Zhu, Xiancan; Song, Fengbin; Liu, Shengqun; Liu, Fulai; Li, Xiangnan
Abstract: Plant can establish a mutualistic symbiosis with arbuscular mycorrhizal (AM) fungi to improve plant growth and resistance to environmental stresses. The aim of this study was to evaluate the effect of AM on nutrient accumulation of wheat ( Triticum aestivum L.) plants under combined elevated CO2 and soil salinity. The effects of CO2 elevation (700 ppm) and salt treatments (0, 1, and 2 g NaCl kg −1 dry soil) on the nutrient accumulation of wheat plants inoculated with AM fungus ( Rhizophagus irregularis ) were investigated. The AM root colonization was decreased by salt treatment and increased by elevated CO2 . AM symbiosis significantly increased shoot dry weight and the accumulation of total C, N, K, Ca, Mg, and Na under elevated CO2 and salt stress. Plant dry biomass was positively correlated with total N, K, Ca, and Mg accumulation, whilst it was negatively correlated with Na accumulation. The concentrations of soluble sugar and glucose in shoots and roots of the AM plants were higher than of the non‐AM plants. It is suggested that AM enhances carbohydrate assimilation and nutrient accumulation in wheat exposed to elevated CO2 and soil salinity.